2007
DOI: 10.1103/physreva.76.013836
|View full text |Cite
|
Sign up to set email alerts
|

Intensity dependence narrowing of electromagnetically induced absorption in a Doppler-broadened medium

Abstract: In this paper, we present a theoretical model for studying the interaction between linearly polarized laser light and near-degenerated Zeeman sublevels for a multiple V-type atomic system of 2 S 1/2 F g =2→ 2 P 3/2 F e = 3 transition in 87 Rb. We have calculated the laser absorption in a Hanle configuration, as well as the amplitudes and the widths of electromagnetically induced absorption ͑EIA͒ in the range of laser intensities from 0.01 to 40 mW/ cm 2 . Our results, showing nonvanishing EIA amplitude, a nonm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Note that the earlier studies have reported the resonance width of up to 20 times smaller than the natural width for D 2 in 87 Rb, using a Laguerre−Gaussian coupling beam [25] and an appropriate beam intensity [24,25]. When all of our 'narrowing' techniques are implemented, the experimental method of ours can be used to build a robust and stable magnetometer using Zeeman sub-levels [26][27][28]. This can be carried out after our experimental setup is modified via addition of a quarter-wave plate placed in front of the cell, so that the ω 0 and ω + beams are orthogonal and circularly polarized (σ ± ).…”
Section: Resultsmentioning
confidence: 99%
“…Note that the earlier studies have reported the resonance width of up to 20 times smaller than the natural width for D 2 in 87 Rb, using a Laguerre−Gaussian coupling beam [25] and an appropriate beam intensity [24,25]. When all of our 'narrowing' techniques are implemented, the experimental method of ours can be used to build a robust and stable magnetometer using Zeeman sub-levels [26][27][28]. This can be carried out after our experimental setup is modified via addition of a quarter-wave plate placed in front of the cell, so that the ω 0 and ω + beams are orthogonal and circularly polarized (σ ± ).…”
Section: Resultsmentioning
confidence: 99%
“…Higher efficiency of the light of elliptical polarization, vs. linearly polarized laser light, at higher laser intensities, can be explained by more efficient pumping to edged magnetic sublevels of the F g = 2. Calculations of the population of the Zeeman sublevels as a function of the laser intensity for linearly polarized light [8] and for elliptically polarized light (not shown) tell that the observed signal depends on the level of optical pumping of the Zeeman sublevels of the ground hyperfine state (orientation). We would like to point out that calculations also show that the observed behavior of the EIA is under strong influence of the Doppler broadening.…”
Section: Resultsmentioning
confidence: 99%
“…The role played by transfer of coherence from the excited to the ground hyperfine state was also analyzed. Our previous work on phenomena of enhanced absorption includes the investigation of EIA amplitudes and linewidths as a function of different parameters, such as laser intensity, polarization and transverse magnetic fields [16]- [18].…”
Section: Introductionmentioning
confidence: 99%